Abnormal Breast Temperature and Cortical Enlargement of the Axillary Lymph Nodes Through the Thermography - Francisco‐J Renero‐C; Tania‐Cristell Martínez‐Azmitia (Clinical Case Reports)
ABSTRACT Breast thermography may be used for the early detection of breast diseases in women younger than 50 years. Performed breast thermography on a woman in her 20s, revealing an average temperature difference of about 1°C. Ultrasound imaging further identified a simple cyst and enlarged, vascularized lymph nodes in both axillae.